Phytochemical and mineral profiling of anti-fertilizer plants used by pygmy women in the town of Mbandaka in the Democratic Republic of the Congo: Case of Ipomoea involucrata P.Beauv. and Piptadeniastrum africanum (Hook.f.) Brenan - Ruth Katunda,; Jean Jacques Amogu,; Nzundu, Jean Paul; Florent Mukeba,; Didier Dianzuangani,; Paulin Mutwale,; Odette Kabena,; Félicien Lukoki, (International Journal of Agricultural Research, Innovation and Technology, 2024)
This study was carried out to determine the phytochemical and mineral composition of Piptadeniastrum africanum (Hook.f.) Brenan and Ipomoea involucrata P. Beauv., two plants presumed anti-fertilizers, were cited during an ethnobotanical survey carried out in 2018 among indigenous women in Mbandaka and the surrounding area. Micrography was carried out, followed by determination of mineral composition by ICP-AES and SAA, and the TLC for a highlight of the various phytochemical compounds making up these two plants. The study determined the relative structure of the multiple cells and tissues making up these plant drugs, including numerous raphids characteristic of Ipomoea involucrata and calcium oxalate crystals characteristic of Piptadeniastrum africanum. Among the chemical compounds, those directly linked to female anti-fertility have been highlighted. These include flavonoids, tannins, phenolic compounds, and terpenoids. Elemental analysis revealed mineral salts and trace elements directly influencing reproduction, such as iron, zinc, calcium, sodium, and arsenic. Even if these data make it possible to justify the activity of these two plants in reproductive health, it is, however, necessary for an in-depth study on the in vitro evaluation to determine the clear anti-fertilizing activity of these plants used, raw, by indigenous women. Int. J. Agril. Res. Innov. Tech. 13(2): 64-69, Dec 2023